DIFFICULTIES OF ASSIGNMENT OF PHRASEOLOGICAL CIRCUMSTANCES AND RUSSIAN WORDS BY UZBEK STUDENTS - Irbutaeva Nigora Dilshodovna (International Engineering Journal For Research & Development, 2021)
In this article, special attention is paid to the peculiarities of the fact that in many non-Russian-language schools the requirements for reinforcement, repetition of the student's lexical minimum are not fulfilled. On the difficulty in the assimilation of Russian words by students. An important role is played by constant speech training, which is practically absent in the classroom of the Russian language.